2003
DOI: 10.1007/s00335-003-2277-9
|View full text |Cite
|
Sign up to set email alerts
|

A strategy for the integration of QTL, gene expression, and sequence analyses

Abstract: Although hundreds if not thousands of quantitative trait loci (QTL) have been described for a wide variety of complex traits, only a very small number of these QTLs have been reduced to quantitative trait genes (QTGs) and quantitative trait nucleotides (QTNs). A strategy, Multiple Cross Mapping (MCM), is described for detecting QTGs and QTNs that is based on leveraging the information contained within the haplotype structure of the mouse genome. As described in the current report, the strategy utilizes the six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
51
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 42 publications
5
51
0
Order By: Relevance
“…Kcnj9 has been identified as the likely quantitative trait gene controlling basal locomotor behavior (39). Kcnj9 is highly expressed in strains with low basal locomotor activity.…”
Section: Discussionmentioning
confidence: 99%
“…Kcnj9 has been identified as the likely quantitative trait gene controlling basal locomotor behavior (39). Kcnj9 is highly expressed in strains with low basal locomotor activity.…”
Section: Discussionmentioning
confidence: 99%
“…They found that 31% of these genes are heritable and median heritability is 0.34. Additional studies have been carried out in yeast (Brem et al 2002), mouse (Hitzemann et al 2003;Bystrykh et al 2005;Chesler et al 2005), rat (Hubner et al 2005), and human (Morley et al 2004) mapping populations.…”
mentioning
confidence: 99%
“…6,7 Another approach to reduce the number of candidate genes is to investigate the expression of the genes in the QTL. 8,9 In this way, polymorphisms in regulatory or promoter regions resulting in differences in mRNA expression will be detected. This kind of experiment is well suited in a distinct system like a congenic strain, where the noise of genetic differences between strains is reduced.…”
Section: Introductionmentioning
confidence: 99%